REVIEW OF BOOK BY V. GRESHCHUK - Bachkur, R. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Review of book of Greshchuk V. “Studio from Ukrainian linguistics: Chosen labors” / V.Greshchuk. – Ivano-Frankivsk: Misto-NV, 2009. – 520 s.